KONTRIBUSI PEMIKIRAN FATIMA MERNISSI TERHADAP PENGEMBANGAN TEOLOGI ISLAM KONTEMPORER BERPERSPEKTIF GENDER - Muhammad RayhanRasmi Faizal; Della Puspita Sari; Marsyia Marsyia; Adrian Fajri; Abdul Halim Maulana (JURNAL AL-AQIDAH, 2026)
This article examines the contribution of Fatima Mernissi's thought to the development of contemporary Islamic theology from a gender perspective through a qualitative library research approach. By analyzing Mernissi's major works and relevant scholarly literature, this study finds that her reinterpretation of Qur'anic verses and critical examination of hadith challenge patriarchal interpretations that have long shaped theological discourse in many Muslim societies. Rather than viewing gender inequality as an essential teaching of Islam, Mernissi demonstrates that it is largely the product of historical, social, and cultural constructions reflected in male-centered interpretations of religious texts. Her feminist hermeneutical approach promotes a theological framework grounded in justice, equality, and human dignity, while reaffirming women's equal rights in education, leadership, and public participation. The study further shows that Mernissi's ideas remain relevant to the Indonesian context, where efforts to integrate gender justice into Islamic scholarship continue to expand through academic and religious institutions. The main contribution of this research lies in demonstrating that Mernissi's thought provides a significant conceptual foundation for reconstructing contemporary Islamic theology toward a more contextual, inclusive, and gender-responsive paradigm. Accordingly, this study argues that gender equality should be recognized not merely as a social agenda but as an integral theological principle in the ongoing development of contemporary Islamic thought.